2016
DOI: 10.1108/oir-02-2015-0062
|View full text |Cite
|
Sign up to set email alerts
|

Informing brand messaging strategies via social media analytics

Abstract: Purpose – The purpose of this paper is to offer a theory-driven, evidence-based approach to developing a brand’s messaging strategies on social media encompassing three messaging dimensions, namely, appeal, content, and richness. Design/methodology/approach – Using longitudinal data from three Fortune 200 companies – Delta Airlines, Wal-Mart, and McDonald’s – the authors empirically investigate comprehensive strategic messaging framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 15 publications
2
59
1
Order By: Relevance
“…Figure 1 illustrates the overall research model. From the perspective of vividness and richness of online UGC, reviews and comments are only text messages and are characterised as low level of vividness and richness (Coursaris et al, 2016;Luarn et al, 2015). Previous research obtains mixed results regarding the influence of valence of users' reviews (i.e., whether comments are positive or negative) on sales (Floyd et al, 2014;You et al, 2015) and other psychological outcomes (Purnawirawan et al, 2015).…”
Section: Hypotheses Developmentmentioning
confidence: 91%
See 4 more Smart Citations
“…Figure 1 illustrates the overall research model. From the perspective of vividness and richness of online UGC, reviews and comments are only text messages and are characterised as low level of vividness and richness (Coursaris et al, 2016;Luarn et al, 2015). Previous research obtains mixed results regarding the influence of valence of users' reviews (i.e., whether comments are positive or negative) on sales (Floyd et al, 2014;You et al, 2015) and other psychological outcomes (Purnawirawan et al, 2015).…”
Section: Hypotheses Developmentmentioning
confidence: 91%
“…Discussions developed by users in the forum section of OBCs are also characterised as low level of vividness and richness in this research, mainly because the content found in these discussions is text based (Coursaris et al, 2016;Luarn et al, 2015). Previous research offers evidence about the role of UGC in forums/discussions in performance measures, such as product adoption.…”
Section: Low Level Vividness and Richness: Positive And Negative Commmentioning
confidence: 98%
See 3 more Smart Citations